Neurosonography and pathology in the Schinzel-Giedion syndrome. - Maclennan, A C (1991)
We describe a case of the Schinzel-Giedion syndrome, where increasing ventriculomegaly, intraventricular bands, and subependymal pseudocysts were shown by ultrasound of the head. Subsequent neuropathology confirmed the hydrocephalus.